The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1369433218807685
|View full text |Cite
|
Sign up to set email alerts
|

Lateral load behaviour of a rectangular precast shear wall involving vertical bolted connections

Abstract: This article is concerned about precast reinforced concrete shear walls and the methods of assembling shear wall panels to form a reliable load transfer system. An assembling method is proposed using dry connection through an H-shaped steel connector (H-connector) and high-strength bolts. A preliminary design, including the H-connector design and bolt design, has been carried out based on the force analysis on the vertical connection in the wall assembly. On the basis of the finite element analysis verified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The interactions between the segments also consist of two parts: (1) the interaction between the sealing gasket and the segment and (2) the interaction between the surfaces of the segment edge. These interactions are simulated by ''face-to-face'' contact elements (TARGE170 and CONTA174) which can simulate cold interface conditions transmitting only compression force in the normal direction and shear force in the tangential direction (Sun et al, 2019). In common conditions, the friction coefficient of concrete is 0.3-0.4.…”
Section: D Numerical Modelmentioning
confidence: 99%
“…The interactions between the segments also consist of two parts: (1) the interaction between the sealing gasket and the segment and (2) the interaction between the surfaces of the segment edge. These interactions are simulated by ''face-to-face'' contact elements (TARGE170 and CONTA174) which can simulate cold interface conditions transmitting only compression force in the normal direction and shear force in the tangential direction (Sun et al, 2019). In common conditions, the friction coefficient of concrete is 0.3-0.4.…”
Section: D Numerical Modelmentioning
confidence: 99%
“…A precast shear wall system utilizing high-strength bolts and H-shaped steel frames was proposed [27], in which the steel frames covered the entire horizontal and vertical joints to connect the adjoining panels. Subsequent experimental and analytical studies [28][29][30][31][32] showed that the integrated bolted connectors were capable of providing sufficient strength to effectively join the adjacent panels together. This wall system exhibited satisfactory seismic performance matching with the cast-in-situ concrete structure [33].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical connections have been tested based on 29 specimens to determine their capacity and stiffness 9 . Horizontal connections like the mild steel connections 10 and H‐shaped steel connector 11 are proposed and investigated. Results show that a proper designed connection has similar seismic performance compared with cast‐in‐situ shear wall, which can meet the seismic design requirements.…”
Section: Introductionmentioning
confidence: 99%